Injectable Biomimetic Hydrogel Constructs for Cell-Based Menopausal Hormone Therapy with Reduced Breast Cancer Potential - Yang, Chungmo; Yang, Heeseon; Kim, Hyerim; Chung, Nanum; Shin, Jungwoo; Min, Hyewon; Lee, Kangwon; Lee, Jung Ryeol (Biomaterials research, 2024)
Hormone replacement therapy (HRT) has been a primary method in menopausal women and patients with ablated ovaries, but safety has been a concern. Cell-based HRT has emerged as an alternative approach without side effects causing pharmaceutical HRT via 3-dimensionally engineered constructs layering ovarian hormone-producing cells. In this study, we applied micro-sized ovarian cell-laden hydrogel beads as an approach to cell-based HRT using a minimally invasive method in the menopausal rat model. Here, we constructed GC/TC-laden microbeads (GTBs; GC, granulosa cell; TC, theca cell) that allow crosstalk between endocrine cells, encapsulating multiple beads for the figuration of the original ovary. We assessed the ovarian hormone production function of GTB through in vitro culture for 90 days. We applied it to a menopausal rat model and confirmed that GTB-injected rats restored their endocrine function, leading to the regeneration of the thinned endometrium and the maintenance of regular estrous cycles in some individuals. Additionally, it was observed to alleviate menopausal symptoms, including body weight gain and osteoporosis. Notably, the GTB-injected rats did not show mammary gland hyperplasia observed in the pharmaceutical HRT groups and exhibited fewer p53- and KI67-positive and an increase in phosphatase and tensin homolog-positive mammary gland epithelial cells compared to pharmaceutical hormone-treated rats. These results suggest that GTB-based HRT could present a lower risk of breast cancer compared to conventional pharmaceutical-HRT use. Our study highlights the potential of cell-based HRT using an injectable artificial ovary, offering a safer alternative for women requiring HRT.